1999
DOI: 10.1037/0022-006x.67.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Normative comparisons for the evaluation of clinical significance.

Abstract: This article initiates the special section on clinical significance. Within a brief précis and overview, the 4 methodological articles and the integrative commentary of the special section are introduced. A call for the inclusion of the assessment of clinical significance in treatment evaluations is extended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
407
0
7

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(420 citation statements)
references
References 18 publications
3
407
0
7
Order By: Relevance
“…Two methods were used to demonstrate whether the treatment resulted in clinically significant change (Kendall et al, 1999). First, we observed that reliable change had been achieved (Reliable Change Index).…”
Section: Designmentioning
confidence: 99%
“…Two methods were used to demonstrate whether the treatment resulted in clinically significant change (Kendall et al, 1999). First, we observed that reliable change had been achieved (Reliable Change Index).…”
Section: Designmentioning
confidence: 99%
“…In so doing, readers will be able to better gauge the extent to which improvement on these measures is indicative of change that is of practical importance to the participant. A number of methods for assessing clinical significance have been proposed [70][71][72][73]. However, as Kazdin [72] notes, clinical significance should be determined by the goals of an intervention.…”
Section: Literature Focuses On Statistical Significance With Little Amentioning
confidence: 99%
“…This shows that even children who received a relatively small dose of the full intervention were affected. 8 We also evaluated the impact of the early intervention in terms of clinical significance (Kendall, Marrs-Garcia, Nath, & Sheldrick, 1999). We calculated T scores for TRF Externalizing scale scores using the standardization scales published by Achenbach (1991).…”
Section: Additional Analyses Regarding Aggression Effectsmentioning
confidence: 99%